2022
DOI: 10.22495/jgrv11i2siart8
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment, economic growth, and unemployment: Evidence from developing countries

Abstract: High unemployment is one of the major difficulties confronting most modern countries, putting social, economic, and political strain on policymakers. Foreign direct investment (FDI) is critical to a country’s economic development, particularly in transitional economies. FDI is a major source of capital inflows to developing countries. FDI affects the level of employment in the host country, in addition to its many other effects. The research is based on the studies of Johnny, Timipere, and Krokeme (2018) and Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Thus, OECD (2020) shows that the presence of FDI in the six selected developing countries in the MENA region can significantly reduce the unemployment rate. This is in line with the research by Kukaj et al (2022) Our study finds that the coefficient of GDP is negative (-0.042), meaning that if the GDP goes up by 1%, the unemployment rate will go down by 0.042%, holding other variables constant. The results of this study accept Okun's law on the relationship between economic growth and unemployment.…”
Section: The Alternative Hypothesis Fixed Effects Modelsupporting
confidence: 92%
See 4 more Smart Citations
“…Thus, OECD (2020) shows that the presence of FDI in the six selected developing countries in the MENA region can significantly reduce the unemployment rate. This is in line with the research by Kukaj et al (2022) Our study finds that the coefficient of GDP is negative (-0.042), meaning that if the GDP goes up by 1%, the unemployment rate will go down by 0.042%, holding other variables constant. The results of this study accept Okun's law on the relationship between economic growth and unemployment.…”
Section: The Alternative Hypothesis Fixed Effects Modelsupporting
confidence: 92%
“…Alalawneh & Nessa (2020)'s earlier study on unemployment in the Middle East and North Africa over the period 1990-2018 revealed that foreign direct investment (FDI), inflation rates, and exports influence unemployment in MENA nations. Several other studies find similar results, including Febryastuti (2019); Kukaj et al (2022); Marzan et al (2020);and Zeb et al (2014). Nonetheless, there are also a number of contradicting and divergent studies, such as Aktar & Ozturk (2009); Johnny et al (2018);and Tegep et al (2019), which find that these macroeconomic factors have no effect on the unemployment rate.…”
Section: Introductionmentioning
confidence: 78%
See 3 more Smart Citations